Menumbuhkan Kreatifitas dan Kewirausahaan Masyarakat Desa Nirannuang Kecematan Bontomarannu Melalui Sosialisasi Pemanfaatan Limbah sebagai Bahan Pembuatan Paving Blok - Aeni, Nur; Sari, Desy Nurhasanah; Ansyarif, Azmaleni Rifkah (Yayasan Daarul Huda Kruengmane, 2024)
Waste is defined as something that is no longer used, unused, disliked or something that is thrown away, which comes from human activities and does not occur by itself or remains from a business or activity in the form of piles of used goods, animal waste, plants or vegetables. Environmental balance becomes disturbed if the amount of waste products exceeds the environmental tolerance threshold and causes damage and can have a negative impact on human health. So it is necessary to handle waste, one way to process waste to make it more useful is by making Paving Blocks. In Nirannuang Village, Bontomarannu District, the community was given training on how to use waste such as plastic waste, used oil waste and sugarcane bagasse waste as material for making paving blocks. The aim is to expand the creativity of the people of Nirannuang Village, Bontomarannu District and help them create independent businesses that can improve their own economy and that of the surrounding community. Training is carried out by delivering speeches and interactive discussions. The results of the socialization show that the understanding of the people of Nirannuang Village, Bontomarannu District in entrepreneurship has increased significantly, as evidenced by a questionnaire regarding interest in exploring making Paving Blocks from plastic waste, which has increased by 90%. Apart from that, the community was very enthusiastic and fully participated in the stages of socialization activities.